Formulation of a Novel Nanoemulsion System for Enhanced Solubility of a Sparingly Water Soluble Antibiotic, Clarithromycin. (23rd March 2014) - Vatsraj, Stuti; Chauhan, Kishor; Pathak, Hilor
Abstract : The sparingly water soluble property of majority of medicinally significant drugs acts as a potential barrier towards its utilization for therapeutic purpose. The present study was thus aimed at development of a novel oil-in-water (o/w) nanoemulsion (NE) system having ability to function as carrier for poorly soluble drugs with clarithromycin as a model antibiotic. The therapeutically effective concentration of clarithromycin, 5 mg/mL, was achieved using polysorbate 80 combined with olive oil as lipophilic counterion. A three-level three-factorial central composite experimental design was utilized to conduct the experiments. The effects of selected variables, polysorbate 80 and olive oil content and concentration of polyvinyl alcohol, were investigated. The particle size of clarithromycin for the optimized formulation was observed to be 30 nm. The morphology of the nanoemulsion was explored using transmission electron microscopy (TEM). The emulsions prepared with the optimized formula demonstrated good physical stability during storage at room temperature. Antibacterial activity was conducted with the optimized nanoemulsion NESH 01 and compared with free clarithromycin. Zone of inhibition was larger for NESH 01 as compared to that with free clarithromycin. This implies that the solubility and hence the bioavailability of clarithromycin has increased in the formulated nanoemulsion system.